Islamic banking towards sustainable green finance and corporate social responsibility - Sharofiddin, Ashurov; Al-Shaghdari, Fahd Mohammed Obad; Zakariyah, Habeebullah; Habibullah, Mohammad (Routledge (Taylor & Francis Group), 2024)
This study presents a bibliometric analysis of the value and financial performances of Islamic banks in the context of green finance and sustainable social responsibility. Employing comprehensive data extraction from scholarly databases such as Scopus, the study systematically quantifies and maps literature trends, influential works, and emergent themes since the establishment of the Islamic banking system. The methodological framework consists of comprehensive data collection, preprocessing, analysis, and visualization procedures. The secondary data sources include academic databases like Scopus and yielded 69 scholarly articles, conference papers, and other academic writings. Keyword-based search queries combining terms such as “Islamic Banks”, “Green Finance”, “Social Responsibility”, “Sustainability”, and “Financial Performance” are utilized. The findings indicate an increasing academic interest in the integration of sustainability principles within Islamic banking. Leading clusters revealed a strong focus on value-creation mechanisms rooted in Shari'ah-compliant green finance initiatives and the broader implications for sustainable social responsibility. Such detailed analysis facilitates understanding trends, strengths, weaknesses, and knowledge gaps within this growing field. The results underline the importance of aligning Islamic banking operations with global sustainability needs and offer insights for scholars, practitioners, and policymakers to further strengthen the bridge between Islamic financial ethics and contemporary green initiatives.